2007
DOI: 10.1007/s12010-007-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Urease from Pigeonpea (Cajanus cajan) on Agar Tablets and Its Application in Urea Assay

Abstract: The gene for the Cu, Zn-superoxide dismutase (SOD) from the yeast Saccharomyces cerevisiae was cloned, characterized, and overexpressed in the methylotrophic Pichia pastoris. The sod gene sequence obtained is 465 bp and encodes 154 amino acid residues. The sod gene sequence was cloned into the pPIC9K vector, yielding pAB22. The linearized pAB22 DNA, digested with restriction enzyme SacI, was transformed into the genome of the GS115 strain of the yeast P. pastoris. The SOD was purified from the cultured yeast b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…In the present case, lower glycosylation in case of urease from C. ensiformis is responsible for lesser immobilization efficiency than urease from C. cajan (www.brenda-enzymes.org). The immobilization efficiencies of urease obtained from C. ensiformis and C. cajan onto AuNps are significantly higher than previous reports on urease immobilization onto various matrices [9][10][11][12][13][14][15][16][17][21][22][23][24][25][26]. …”
Section: Optimization Of Nano-urease From C Ensiformis and C Cajanmentioning
confidence: 67%
See 2 more Smart Citations
“…In the present case, lower glycosylation in case of urease from C. ensiformis is responsible for lesser immobilization efficiency than urease from C. cajan (www.brenda-enzymes.org). The immobilization efficiencies of urease obtained from C. ensiformis and C. cajan onto AuNps are significantly higher than previous reports on urease immobilization onto various matrices [9][10][11][12][13][14][15][16][17][21][22][23][24][25][26]. …”
Section: Optimization Of Nano-urease From C Ensiformis and C Cajanmentioning
confidence: 67%
“…Partitioning effects on K m have been discussed in various reports on enzyme immobilization [33][34][35]. Nano-ureases from C. ensiformis and C. cajan have significantly improved kinetic parameters with respect to previous studies on urease immobilization [12][13][14][15][16][17][18][21][22][23][24][25][26].…”
Section: Steady State Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the optimum temperature of free tannase was 45 C, whereas that of immobilized tannase was 35 C (Figure 1a).The optimum temperature decreased by 10 C after immobilization. Generally, immobilization may enhance or not change the optimum temperature of enzyme (Neerupma et al, 2006;Mulagalapalli et al, 2007;Makkar, 1982;Roila et al, 2007;Bruno et al, 2005). There are few reports that immobilization decreases the optimum temperature.…”
Section: Characteristics Of Immobilized Tannasementioning
confidence: 99%
“… 16 Due to the higher lifetime and stability of chemically bonded enzymes, chemical immobilization (CI) of urease is more feasible 17 than physical adsorption 18 or encapsulation, 19–21 although CI leads to some enzyme activity loss. 22 In this context, the immobilization of urease on cellulose, 9 chitosan, 23 alginate, 24 gelatin, 25 and agar 26 have been tried to achieve urea biosensors. 27,28 Kumar et al 24 prepared the biosensor alginate@urease and compared it with chitosan@urease for urea detection.…”
Section: Introductionmentioning
confidence: 99%